EFL University Students' Attitudes Toward the Use of Code-switching in English Learning Content on TikTok in Supporting English Language Learning - Yusi Nurhasanah; Siti Sopiah; Riki Ruswandi (FKIP - Universitas Riau, 2026)
TikTok has provided EFL students with various learning content. However, studies that have examined how students perceive code-switching and whether they depend on their first language when learning English through digital platforms are still limited. This study aimed to explore EFL students' attitudes toward code-switching in English-learning content on TikTok and to identify their level of first-language dependency. This study employed a descriptive quantitative research design with 71 students from the Faculty of Teaching Training and Education at a private university in Bandung, Indonesia. Data were collected through a Likert-scale questionnaires compromising three dimensions: cognitive, behavior, and affective. The questionnaires were analyzed using descriptive statistics. The findings showed that students had positive attitudes toward code-switching, with an overall mean score of 4.09. Among the three dimensions, the cognitive dimension obtained the highest mean score (M = 4.27), followed by the affective dimension (M = 4.07) and the behavioral dimension (M = 3.93). In terms of first language dependency, the participants tend to be at a moderate level (M = 3.30). These findings indicate that code-switching can serve as a useful learning support strategy that helps students to understand English content without highly dependent on the use of the first language.